Health impact of exposure to arsenic-contaminated drinking water in Vietnam - Bui Huy Tung; Tran Thi Tuyet Hanh; Hong, N.N.; Hung Nguyen-Viet (2012)
The public health situation of the population of Hanam Province in Vietnam is of great concern, as it is exposed daily to arsenic-contaminated drinking water. Optimising arsenic (As) removal efficiency of current sand filters at household level or switching to cleaner or As-free water sources is crucial to prevent or reduce community health risks.